Uma leitura junguiana sobre as motivações de casais pretendentes à adoção - Souza, Janaína Ramalho Ferraz Pereira de (2021)
Adoption is a legal procedure that attributes the status of biological child to the adoptee, with all the rights and duties, including inheritance, legally disconnecting him from the bond with the biological parents, except for marriage impediments. In Brazil, the Child and Adolescent Statute establishes that applicants for adoption undergo psychosocial assessment and legal preparation by the Children and Juvenile Court technical staff, aiming to ensure the smooth progress of the adoption process. Notwithstanding those efforts, in her role as a judicial psychologist the researcher has encountered that in some cases adopters do return adoptees to public authorities. On the one hand, for the child that experience tends to constitute a painful mark that recalls and reiterates the primary experience of abandonment by biological parents. On the other hand, it may be seen as the result of the adoptive parents’ the lack of elaboration of the unconscious reasons that determined the adoption and came to negatively influence parent-child bonding. However, there is a scarcity of Jungian studies on such motivations. Therefore, the present study aimed at understanding, from the perspective of Analytical Psychology, the motivations of applicants for adoption registered in the Brazilian National System of Adoption (SNA), thus contributing to the work of judicial psychologists in their efforts to help establish a successful parent-child bonding. Five heterosexual couples, legally married and registered in the SNA, between 29 and 49 years of age, participated in the qualitative research, characteristics that are prevalent in the largest group of applicants registered with the SNA. The instruments used were: sociodemographic questionnaire, semi-open interview and drawing, as an expressive technique. The content of the reports and drawings were analyzed in order to identify common themes and symbolic aspects involved. The following motivations for adoption were found: desire to form a family; desire to exercise paternity/motherhood; desire to have a child. Infertility, in this research, emerged as a path to adoption. The analysis of participants' reports and drawings from the perspective of analytical psychology suggests that the constellated archetypes were as follows: family, mother, father and divine child